PENGARUH DEEP BREATHING EXERCISE TERHADAP NYERI HAID (DISMENORE) DI PERUMAHAN WAHYU TAMAN SARIROGO DESA SUMPUT KECAMATAN SIDOARJO - Geby Sarawati Harnoko; Agung Hadi Endaryanto; Achmad Fariz; Nurul Halimah (PROFESSIONAL HEALTH JOURNAL, 2023)
Introduction: Dysmenorrhea is menstrual pain that is actually not so dangerous for adolescent girls but their complaints can hinder daily activities with varying degrees of pain for each person (Ibrahim et all., 2020). Methods: This study uses quasi-experimental research with the type of 1 group design before and after the test, the type used is the manipulation of free or flexible variables with the number of respondents 15 adolescent women aged 15-20 years using NRS (Numeric Rating Sacle) measurements. Results: From the results of the analysis test with paired T-Test there is an influence on the initial and final variables, because the significance value shows (2 tailed) p=0.000, <0.05 So it can be concluded that <0.05 can correlate, namely there is a significant effect on deep breathing exercise on menstrual pain or dysmenorrhea. Conclusion: the provision of deep breathing exercises is proven to have an effect on respondents with complaints of menstrual pain or dysmenorrhea.